Laparoscopic proctocolectomy with ileal j-pouch anal anastomosis in children - Ateş, Ufuk; Ergün, Ergun; Göllü, Gülnur; Küçük, Gönül; Yağmurlu, Aydın (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: We aimed to evaluate postoperative fecal incontinence scales of children who underwent laparoscopic proctocolectomy and ileal J-pouch anastomosis for familial adenomateous polyposis (FAP) and inflammatory bowel disease (IBD). Materials and Methods: Fecal incontinence scores were collected at 3 months post-surgery. A retrospective chart review was also performed to obtain the demographic data and operative technical details. Results: The postoperative Wexner Fecal Incontinence Score was 0 in 9 of 11 patients and satisfactory in the remaining two. None of the children had a major complication. Conclusion: Even though the presented study does not have any comparable data, it seems that laparoscopic total proctocolectomy with ileal J-pouch anal anastomosis (TP IPAA) might be the best choice of surgery because it provides good continence with low complication rates. Cite this article as: Ateş U, Ergün E, Göllü G, Küçük G, Yağmurlu A. Laparoscopic proctocolectomy with ileal j-pouch anal anastomosis in children. Turk J Gastroenterol 2017; 28: 384-7.a